Energy Performance in Buildings and Quality of Life - Fabbri, Kristian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Buildings allow several kinds of human activity: work, eat, sleep, play, etc., and they have a role in determining quality of life: ugly and uncomfortable buildings can be the worst place to live. The energy performance of buildings has a special role in improving and guaranteeing quality of life because it concerns architectural design, energy cost, consumption and energy poverty, and thermal comfort-both indoor and outdoor. Following a multidisciplinary approach, we present several case studies and articles about the correlation between building and quality of life. The included research highlights the relationship between BEP and quality of life in terms of wellbeing and thermal comfort and household smartness following UE Directive 844/2018, as well as the reduction of energy poverty and the impact of buildings on the environment and global warming. Also in this book is a city-scale study that attempts to evaluate the effect of climate change on building performance and building energy efficiency mapping and, moreover, reports some cases of indoor environment quality as well as thermal comfort in nearly zero energy buildings; finally, detailed scientific literature on energy poverty and outdoor wellbeing quality of life are presented.